Life through my eyes a teacher's little steps towards perfection - Muhamad Hafiz Ismail 1986- (MPH Group Publishing Sdn. Bhd for UCSI University, Kuala Lumpur Campus, 2011)
Muhamad Hafiz bin Ismail, a new Malaysian teacher, is posted to his first school-a primary school in a remote jungle community in Perak-to teach orang asli Temiar pupils. Initially daunted by this challenge, he decides to create a blog to help him document and reflect on his new life and career. Day by day, the process of recording his experiences, in writing and photographs, helps him to stay positive. He devises a myriad of effective and creative approaches to develop his pupils' confidence and love of school and to help them see that learning is fun. He finds innovative ways to help them learn and is devoted to giving them the best. As Hafiz embarks on a journey of self-discovery, he experiences the joys of being a teacher, and grows as a teacher and as a person by taking little steps towards perfection. This inspirational and charming blog about a year in the life of a new teacher is now a book to be enjoyed by parents, new and experienced teachers, or anyone interested in education or real stories on school life. Life Through My Eyes: A Teacher's Little Steps Towards Perfection is a unique and motivating account of how one teacher and his pupils learn and transform together.